ANALISIS PENERAPAN LITERASI DIGITAL TERHADAP MINAT BACA SISWA KELAS V SD - Setyaningsih, Clara Dwi; Albertus Hartana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the rapid development of digital technology in education and the low reading interest among elementary school students. Therefore, strategic efforts through the implementation of digital literacy are needed to effectively and contextually enhance students' reading interest. This study aims to analyze the implementation of digital literacy on the reading interest of fifth-grade students at SD Kanisius Sengkan and SD Negeri Perumnas Condong Catur. The research employs a qualitative approach with data collection techniques including interviews, observations, questionnaires, and documentation studies involving the principal, fifth-grade class teachers, ICT teachers, and fifth-grade students. The data obtained goes through stages of reduction, data presentation, and conclusion drawing to describe the planning, implementation, and evaluation of digital literacy, as well as the tendencies of students' reading interest. The research findings indicate that both schools have implemented digital literacy, but they lack structured policy support and evaluation instruments. Implementation is still constrained by limited devices and unstable school internet connectivity. Nevertheless, the utilization of digital media (PPT, videos, e-books, gadgets, and ICT labs) makes students more enthusiastic, focused, and interested in reading compared to using printed books alone. Questionnaire data on reading interest shows that all students in both schools fall into the "good" and "very good" categories, with none in the "fair" or "poor" categories, thus demonstrating that digital literacy implementation enhances the reading interest of fifth-grade students.